Palmar Dermatoglyphics and Idiopathic Epilepsy – A Systematic Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dermatoglyphics is the science which deals with the study of dermal ridge configuration on the digits, palmsand soles. Etymologically this term is harmonious blend of two words Derma – skin; Glyphe – carve. It givesthe impression that something has been carved out of the skin. The entire human body is clothed with theskin which happens to be the largest and most important organ of the body. However, the skin on the ventralsides of the hands and the plantar sides of feet is exclusively designed and is corrugated with the ridgesand configurations which are functionally useful as they help in the grasping without which the objectswould easily slip away from the hands. Dermatoglyphic traits are genetically determined. Dermatoglyphicabnormalities are due to genetic or other factors that express their effect before the end of 5th month of foetaldevelopment. The permanency of finger patterns, the extreme variability from one individual to the otherand easy analysis are some of the reasons for its wide application in a variety of conditions. Abnormality inthe genetic configurations of parents is inherited by children and is reflected in the dermatoglyphic pattern.Hence dermatoglyphic study proves to be a very useful, easily applicable, inexpensive, indispensable toolas an indicator in the diagnosis of hereditary diseases in patients. The etiology of the epilepsies allows aclassification of syndrome features into two groups – idiopathic or cryptogenic epilepsy, which has isolatedprimary symptoms without apparent cause and is probably hereditary and finger print configurations areinherited with an embryonic origin common to nervous system. Their attractions indicate pleiotropic effectsof the genotype responsible for enaphalographic irregularity and convulsive seizures.